Enterococcus faecium and Clostridium butyricum combined with selenium as alternatives to the antibiotic colistin: impacts on growth, cecal fermentation, and immune function in rabbits raised under hot environmental conditions - El-Kholy, Mohamed S.; Bassiony, Samar S.; Al-Sagheer, Adham A.; Alagawany, Mahmoud; Ghonime, Mohammed E.; Elwakeel, Eman A.; Lestingi, Antonia; Elolimy, Ahmed A.; Madkour, Mahmoud; Azzam, Mahmoud M.; Elnesr, Shaaban S. (Frontiers in Animal Science, 2025)
IntroductionThe current study was planned to evaluate the effect of using a combination of selenium (Se)-probiotic rabbit and colistin (COL) as a dietary supplement on growth, nutrient utilization, antioxidant and immune responses, blood metabolites, and cecal fermentation during summer conditions.MethodsOne hundred male New Zealand White rabbits aged 5 weeks with an initial body weight of (692.5 ± 5.19g) were randomly assigned to four groups (25 rabbits each) for 5–13 weeks of age experimental period. Four experimental groups in completely randomized design were used. (1) Control group: rabbits received a basal diet (BD) without any added supplements; (2) COL group: rabbits were given BD supplemented with 120 mg of COL/kg; (3) Se+EF group: rabbits consumed BD enriched with 0.3 mg of selenium plus 1 × 108 cfu of Enterococcus faecium/kg; and (4) Se+CB group: rabbits were fed BD fortified with 0.3 mg of selenium plus 2.5 × 106 cfu of Clostridium butyricum/kg.ResultsDuring overall period (5-13 weeks), body weight gain (BWG) and relative growth rate of rabbits consuming diets supplemented with COL, Se+EF, and Se+CB were greater to those of the control group. BWG (in groups Se+CB and Se+EF) and feed conversion ratio (FCR) (in groups COL and Se+EF) were improved compared with the control group. Malondialdehyde (MDA) values were declined in rabbits supplemented with Se plus probiotic (Se+CB or Se+EF) compared with the COL and control groups. Serum lipid profile in rabbits received selenium-probiotic combination (especially Se+EF) was improved. Furthermore, antioxidant levels were better in rabbits supplemented with Se plus probiotics compared to the control, and immune responses were significantly enhanced (P < 0.05).ConclusionSupplementing the diets of rabbits with a combination of selenium and probiotics (Se+CB or Se+EF) led to improvements in growth, antioxidant and immune responses, blood metrics, and cecal fermentation under heat stress conditions.